2010
DOI: 10.1111/j.1540-8167.2009.01661.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect and Safety of the Antithrombotic Therapies in Patients with Atrial Fibrillation and CHADS2 Score 1

Abstract: In AF patients with CHADS(2) score 1, warfarin was better to prevent ischemic stroke than aspirin without increasing the incidence of major bleeding complications. However, the incidence of minor bleeding was higher in the warfarin group than the aspirin group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 35 publications
2
32
1
Order By: Relevance
“…CHADS2 and CHA2DS2VASc scoring systems are used to stratify the risk in patients as low, moderate and high. Previous trials have demonstated that HF carries a higher risk for thromboembolism compared to other risk factors in these scoring systems (130)(131)(132)(133). Therefore, CHADS2 and CHA2DS2VASc scores may underestimate the real risk in patients with HF.…”
Section: What Precautions Should Be Taken In Risk Stratification and mentioning
confidence: 94%
“…CHADS2 and CHA2DS2VASc scoring systems are used to stratify the risk in patients as low, moderate and high. Previous trials have demonstated that HF carries a higher risk for thromboembolism compared to other risk factors in these scoring systems (130)(131)(132)(133). Therefore, CHADS2 and CHA2DS2VASc scores may underestimate the real risk in patients with HF.…”
Section: What Precautions Should Be Taken In Risk Stratification and mentioning
confidence: 94%
“…In Japan, Inoue et al 27) reported that the annual thromboembolism rates of patients with CHADS2 scores of 0 and 1 were 0.6% and 2.5%, respectively. Two studies focused on AF patients with a CHADS2 score of 1 showed a substantial reduction in stroke in patients taking VKA compared with patients taking antiplatelet drug or no OAC, although there was a tendency of increased bleeding 12,13) . Recently, the CHA2DS2-VASc score was reported to be inadequate for risk stratification among patients with low CHADS2 scores, because the annual stroke rate was nearly 2% for patients with a CHADS2 score of 0-1 16,26) .…”
Section: Discussionmentioning
confidence: 99%
“…Recent cohort studies showed that VKA use was associated with a lower stroke rate in patients with CHADS2 score of 1, compared with antiplatelet or no antithrombotic therapy 10,12,13) . .…”
Section: Introductionmentioning
confidence: 99%
“…The magnitude of such influence, and even if it really exists, cannot be confirmed or refuted with these data. Lee et al 22 , however, after a mean follow-up of 22 months, have shown in a population of 422 patients with AF and CHADS 2 1 that anticoagulation with vitamin K antagonists reduced the incidence of stroke as compared with that on antiplatelet drugs (4.2% vs. 12.9%, respectively; p = 0.008). The bleeding rate was similar in both groups.…”
Section: Used Both Medications; ( †) Of All Patients With Chads 2 ≥ 2mentioning
confidence: 99%